2009
DOI: 10.1093/jxb/erp303
|View full text |Cite
|
Sign up to set email alerts
|

How does sulphur availability modify N acquisition of white clover (Trifolium repens L.)?

Abstract: The role of S in legume growth, N uptake, and N2 fixation was investigated using white clover (Trifolium repens L.) as a model species. We examined whether the effect of sulphate addition on N fixation resulted from a stimulation of host plant growth, a specific effect of S on nodulation, or a specific effect of S on nodule metabolism. Clones of white clover, inoculated with Rhizobium leguminosarum, were grown for 140 d in a hydroponic system with three levels of sulphate concentration (0 mM, 0.095 mM, and 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
71
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 53 publications
13
71
0
5
Order By: Relevance
“…Similar results were obtained by Varin et al (2010) who reported that application of sulfate increased whole plant dry mass, root length and nodule biomass in white clover. Besharati and Rastin (1999) also reported that S application had significant effects on root and shoot dry matter of maize grown in calcareous soils under greenhouse conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were obtained by Varin et al (2010) who reported that application of sulfate increased whole plant dry mass, root length and nodule biomass in white clover. Besharati and Rastin (1999) also reported that S application had significant effects on root and shoot dry matter of maize grown in calcareous soils under greenhouse conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Biological nitrogen fixation, nodulation, and yield of peanut crops are reduced with S-deficiency. Varin et al (2010) examined whether the effect of SO 4 2-addition on nitrogen fixation resulted from a stimulation of host plant growth, a specific effect of sulphur on nodulation, or a specific effect of S on nodule metabolism. The application of sulphate (VI) increased whole plant dry mass, root length, and nodule biomass expressed on a rootlength basis.…”
Section: Resultsmentioning
confidence: 99%
“…Under three different regimes of S supply to growth medium, N absorption followed an increasing trend with S in clover plants as well as the concentration of soluble proteins and nitrogen assimilation-related enzyme activities (Varin et al 2010 ) . Moreover, the depletion of thiol-containing molecules such as glutathione under sulfur deprivation occurs in short time, resulting in an increased incidence of oxidative stress.…”
Section: Sulfurmentioning
confidence: 95%
“…It has been also proposed that the effect of oligonutrient deprivation occurs through an impairment of the acquisition of other major nutrients such as nitrogen, phosphorus, or potassium. For instance, sulfur deprivation caused severe growth arrest in plants of Trifolium repens correlated with a decrease in N fi xation (Varin et al 2010 ) .…”
Section: Oxidative Damage In Citrus Under Stressmentioning
confidence: 99%
See 1 more Smart Citation